2017
DOI: 10.18632/oncotarget.14847
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPβ-1 promotes transformation and chemoresistance in Ewing sarcoma cells

Abstract: CEBPB copy number gain in Ewing sarcoma was previously shown to be associated with worse clinical outcome compared to tumors with normal CEBPB copy number, although the mechanism was not characterized. We employed gene knockdown and rescue assays to explore the consequences of altered CEBPB gene expression in Ewing sarcoma cell lines. Knockdown of EWS-FLI1 expression led to a decrease in expression of all three C/EBPβ isoforms while re-expression of EWS-FLI1 rescued C/EBPβ expression. Overexpression of C/EBPβ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…59,60 In Ewing sarcoma and ovarian cancer, CEBPB could promote tumor cell resistance to chemotherapy. 61,62 In this study, we found that CEBPB promotes the transcription of CPT1A and activates FAO. We confirmed that PGC1α binds to CEBPB and is co-localized to the promoter of CPT1A; knockdown of CEBPB sensitized NPC cells to radiation therapy.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…59,60 In Ewing sarcoma and ovarian cancer, CEBPB could promote tumor cell resistance to chemotherapy. 61,62 In this study, we found that CEBPB promotes the transcription of CPT1A and activates FAO. We confirmed that PGC1α binds to CEBPB and is co-localized to the promoter of CPT1A; knockdown of CEBPB sensitized NPC cells to radiation therapy.…”
Section: Discussionsupporting
confidence: 52%
“…CEBPB expression is associated with overall survival in breast cancer and gastric cancer patients . In Ewing sarcoma and ovarian cancer, CEBPB could promote tumor cell resistance to chemotherapy . In this study, we found that CEBPB promotes the transcription of CPT1A and activates FAO.…”
Section: Discussionmentioning
confidence: 51%
“…The differences in the viscosity between DMEM with and without LA717 were, although statistically significant, not noticeable in the practical handling, as both were able to be handled as a liquid. By comparison, the viscosity of DMEM with agarose was far greater at 0.4%, the concentration employed for soft agar colony formation assays 23 (Supplementary Table S2 ). Furthermore, addition of 0.03% methyl cellulose to the medium resulted in a larger increase in viscosity than 0.03% LA717.…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore notable that Trib1 knockdown suppressed Ewing sarcoma cell growth concomitant with increased levels of C/EBPβ. A recent study suggested that overexpression of C/EBPβ increased the transformation activity of Ewing sarcoma cells, although it did not affect cell proliferation or viability, suggesting that a complex feedback loop may exist in C/EBPβ regulation. Nrg1 encodes neuregulin 1 or heregulin, the predominant ligand for ERBB3, and NRG1/ERBB signals are important in cellular development such as for Schwann cells and the cardiovascular system .…”
Section: Discussionmentioning
confidence: 99%